2021
DOI: 10.3389/fmed.2021.777861
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter 2 Inhibitors Mechanisms of Action: A Review

Abstract: Sodium-Glucose Cotransporter 2 inhibitors (SGLT2i), or gliflozins, are a group of antidiabetic drugs that have shown improvement in renal and cardiovascular outcomes in patients with kidney disease, with and without diabetes. In this review, we will describe the different proposed mechanisms of action of SGLT2i. Gliflozins inhibit renal glucose reabsorption by blocking the SGLT2 cotransporters in the proximal tubules and causing glucosuria. This reduces glycemia and lowers HbA1c by ~1.0%. The accompanying sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 64 publications
0
92
0
3
Order By: Relevance
“…By inhibiting SGLT2, SGLT2 inhibitors lower renal reabsorption of filtered glucose and reduce the renal threshold for glucose, thereby increasing urinary glucose excretion [ 19 , 21 – 27 ]. This reduces HbA1c by approximately 0.6–1.0% [ 8 , 28 ]. SGLT2 inhibitors increase sodium delivery to distal tubules through blocking SGLT2-dependent glucose and sodium reabsorption, which is thought to increase tube-ball feedback and decrease intraglomerular pressure.…”
Section: Essential Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…By inhibiting SGLT2, SGLT2 inhibitors lower renal reabsorption of filtered glucose and reduce the renal threshold for glucose, thereby increasing urinary glucose excretion [ 19 , 21 – 27 ]. This reduces HbA1c by approximately 0.6–1.0% [ 8 , 28 ]. SGLT2 inhibitors increase sodium delivery to distal tubules through blocking SGLT2-dependent glucose and sodium reabsorption, which is thought to increase tube-ball feedback and decrease intraglomerular pressure.…”
Section: Essential Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…SGLT2 inhibitors increase sodium delivery to distal tubules through blocking SGLT2-dependent glucose and sodium reabsorption, which is thought to increase tube-ball feedback and decrease intraglomerular pressure. This may affect a variety of physiological functions, comprising reducing cardiac preload and afterload and downregulating sympathetic nerve activity [ 4 , 19 , 21 – 28 ]. Metabolism is shifted to gluconeogenesis and ketosis, which are thought to have protective effects on the heart and kidneys [ 28 ].…”
Section: Essential Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium-glucose cotransporter-2 (SGLT2) inhibitors are a class of lower blood glucose drugs that increase urinary glucose excretion by inhibiting glucose reabsorption at the proximal tubule in the kidney [ 23 , 24 , 25 ]. Recent studies suggested that SGLT2 inhibitor treatment can reduce hepatic lipid levels and alleviate NAFLD, and has blood glucose-lowering effects [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%